Scoping Review on Play-Based Interventions in Autism Spectrum Disorder - Lucía López-Nieto; Laura María Compañ-Gabucio; Laura Torres-Collado; Manuela Garcia-de la Hera (MDPI AG, 2022)
Play as a therapeutic strategy can help to improve daily functioning in children and adolescents with autism spectrum disorder (ASD). Play-based intervention can thus be an optimal option for treatment of this population. Our aim was to describe play-based interventions used in children and adolescents with ASD. We conducted a scoping review. A peer-reviewed literature search was conducted on PubMed, Scopus, EMBASE, Web of Science and PsycINFO databases. We included experimental studies which analyzed play-based interventions in children and adolescents with ASD, which were published in English/Spanish with full text available. We used three tables elaborated a priori to perform data extraction by two authors. Fifteen studies were included, mostly conducted in Australia and published during the past 10 years. Play-based intervention was categorized into three groups: new technologies, symbolic play or official techniques. Interventions lasted approximately 11 weeks, contained one weekly session of 30-60 min and were delivered by parents and teachers. Play-based interventions using new technologies were the most used. Intervention duration and number of sessions varied between articles. Further studies are needed to create play-based intervention protocols which can be implemented in clinical practice with children and adolescents with ASD, thus promoting evidence-based interventions in this field.